Intrauterine Device Placement During Cesarean Delivery and Continued Use 6 Months Postpartum. Issue 1 (July 2015) - Levi, Erika E.; Stuart, Gretchen S.; Zerden, Matthew L.; Garrett, Joanne M.; Bryant, Amy G.
<x xml:space="preserve">Abstract</x> OBJECTIVE: To compare intrauterine device (IUD) use at 6 months postpartum among women who underwent intracesarean delivery (during cesarean delivery) IUD placement compared with women who planned for interval IUD placement 6 or more weeks postpartum. METHODS: In this nonblinded randomized trial, women who were undergoing a cesarean delivery and desired an IUD were randomized to intracesarean delivery or interval IUD placement. The primary outcome was IUD use at 6 months postpartum. A sample size of 112 (56 in each group) was planned to detect a 15% difference in IUD use at 6 months postpartum between groups. RESULTS: From March 2012 to June 2014, 172 women were screened and 112 women were randomized into the trial. Baseline characteristics were similar between groups. Data regarding IUD use at 6 months postpartum were available for 98 women, 48 and 50 women in the intracesarean delivery and interval groups, respectively. A larger proportion of the women in the intracesarean delivery group were using an IUD at 6 months postpartum (40/48 [83%]) compared with those in the interval group (32/50 [64%], relative risk 1.3, 95% confidence interval 1.02–1.66). Among the 56 women randomized to interval IUD insertion, 22 (39%) of them never received an IUD; 14 (25%) never returned for IUD placement, five (9%) women declined an IUD, and three (5%) had a failed IUD placement. CONCLUSION: Intrauterine device placement at the time of cesarean delivery leads to a higher proportion of IUD use at 6 months postpartum when compared with interval IUD placement. LEVEL OF EVIDENCE: I